2010
DOI: 10.1017/s0317167100010751
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum and Cingulum Tractography in Parkinson's Disease

Abstract: Parkinson's disease (PD) is a common progressive neurodegenerative movement disorder. Although motor symptoms are associated with focal loss of substantia nigra dopaminergic neurons, pathological changes in PD are widespread 1 . Dementia in patients with PD is common and patients with Parkinson's disease and dementia (PDD) have involvement of additional cortical regions compared with nondemented PD patients 2 . While PD is not known to directly affect white matter fiber tracts, changes in these tracts may refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 29 publications
3
25
2
1
Order By: Relevance
“…It has been shown that the deterioration of the corpus callosum genu is linked to PD dementia (Kamagata et al, 2013b), as well as executive and attention dysfunctions (Zheng et al, 2014). DTI of the corpus callosum (in the body and the splenium) can help differentiating PD patients according to their cognitive status (normal, mild cognitive impairment, or dementia; Deng et al, 2013); for this purpose, MD demonstrated to be more accurate than FA (Wiltshire et al, 2010). In addition, structural alteration of the corpus callosum, shown using DTI, seems to be involved in predominant gait disorders (Chan et al, 2014) and impulse control disorders (Yoo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the deterioration of the corpus callosum genu is linked to PD dementia (Kamagata et al, 2013b), as well as executive and attention dysfunctions (Zheng et al, 2014). DTI of the corpus callosum (in the body and the splenium) can help differentiating PD patients according to their cognitive status (normal, mild cognitive impairment, or dementia; Deng et al, 2013); for this purpose, MD demonstrated to be more accurate than FA (Wiltshire et al, 2010). In addition, structural alteration of the corpus callosum, shown using DTI, seems to be involved in predominant gait disorders (Chan et al, 2014) and impulse control disorders (Yoo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of dopaminergic neurons in the substantia nigra is considered the hallmark neuropathological finding of PD [9,10]. Yet it is evident that the white matter pathological changes go beyond the basal ganglia, as shown by significant white matter deterioration in the cingulum [11,12] corticospinal tract, corpus callosum [13], and projection fibers along the thalamus, putamen, temporal, and frontal cortices [10,14]. …”
Section: Introductionmentioning
confidence: 99%
“…However negative comparisons results between PD, PDD, and CON have also been reported in regions such as the cingulum and corpus callosum [12]. Additional DTI studies examined individuals with Lewy body dementia (LBD), which presents with early cognitive changes as well as parkinsonism and has a pathology similar to PDD [21].…”
Section: Introductionmentioning
confidence: 99%
“…This important structure is the major fiber tract which connects the homologous cortical areas of the left and right hemisphere [49]. The three dimensional (3D) surface of the corpus callosum can be delineated with the powerful DTI, while it is difficult for the traditional MRI modalities.…”
Section: Resultsmentioning
confidence: 99%